Data in online database 'Brecht's Works in English: a Bibliography' - Silberman, M; Ryland, C; Imbrigotta, K (University of Wisconsin-Madison, 2005)
The online database is hosted by the University of Wisconsin Digital Collections Center and includes bibliographical citations for: dialogues, journals, diaries, essays, interviews, letters, plays, monologues, screenplays, poems, prose and songs. Its search feature can be used to locate entries by keywords in the entire database or to perform a guided search of specific fields. Users may search, for example, by genre, translator’s name, publisher, or any other field descriptor.